2018
DOI: 10.1159/000492003
|View full text |Cite
|
Sign up to set email alerts
|

Joining Parents' Bed at Night and Overweight among 2- to 6-Year-Old Children - Results from the ‘Healthy Start' Randomized Intervention

Abstract: Objective: Parental and child co-sleeping has been suggested as a risk factor for short sleep duration and poor sleep quality that may lead to overweight. We examined if joining parent's bed during night was associated with child overweight. Methods: Cross-sectional data from the ‘Healthy Start' study including 635 2- to 6-year-old Danish children, who were all considered obesity prone. Of these, 496 children had complete information on BMI and whether the child joined parents' bed during night and if so, how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…22 There are mixed studies on the association of co-sleeping and obesity; in a Danish study of 2-6 year old children, co-sleeping was associated with a decreased risk of overweight. 23 There is a need for more research into obesity risk for nighttime formula intake compared to nighttime breastmilk intake.…”
Section: Role Of Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…22 There are mixed studies on the association of co-sleeping and obesity; in a Danish study of 2-6 year old children, co-sleeping was associated with a decreased risk of overweight. 23 There is a need for more research into obesity risk for nighttime formula intake compared to nighttime breastmilk intake.…”
Section: Role Of Sleepmentioning
confidence: 99%
“…28 Numerous studies have also found associations between parenting styles and childhood obesity: authoritative styles are more protective than permissive. 22,23 Notably, controlling and permissive styles have been found in Hispanic families that may contribute to overfeeding. [29][30][31] Research into infant obesity prevention focuses on responsive feeding, recommending parents pay close attention to hunger and satiety cues, but limiting feeding at other times, i.e.…”
Section: Role Of Sleepmentioning
confidence: 99%
“…Co-sleeping varies by culture and was found to occur at a higher rate in Hispanic families compared to white families [ 27 ]. There are mixed studies on the association of co-sleeping and obesity; in a Danish study of 2–6 year old children, co-sleeping was associated with a decreased risk of overweight [ 28 ].…”
Section: Introductionmentioning
confidence: 99%